Postural stability of canoeing and kayaking young male athletes during quiet stance - Stambolieva, K.; Diafas, V.; Bachev, V.; Christova, L.; Gatev, P. (European Journal of Applied Physiology, 2012)
We studied the postural stability of 23 canoeing and kayaking young athletes and 15 healthy untrained age matched subjects during quiet and sensory conflicted stance (standing on stable and foam support with open and closed eyes). We measured with a force platform the center of pressure excursions and applied mean sway amplitude (MA), mean sway velocity (SV) and their Romberg ratios, and sway dispersion index to evaluate standing balance. During standing with eyes open, the athletes in comparison to non-athletes showed in sagittal and frontal plane greater MA and SV when the support was stable and smaller MA and SV when it was unstable. During standing with eyes closed, there were no differences between groups when the support was stable, however, the athletes sway faster and have smaller MA than controls while standing on the foam support. During standing on stable support, Romberg ratios for MA and SV revealed that unlike non-athletes the athletes` MA and SV were vision independent. However, while standing on unstable support the athletes` MA and SV became vision dependent and even greater for the medio-lateral sway. Canoeists` SV vision dependency in both planes was greater than for other groups. These results are in line with our hypothesis that young kayaking and canoeing athletes have a different from non-athletes model of sensory integration due to their specific sporting activity. One possible mechanism of this model may be a subtle re-adaptation deficit after disembarking to stable ground with diminished sensitivity of vision and vestibular apparatus.